The Impact of Sharia Financial Literacy, Religiosity, and Perceived Quality on Investment Decisions on Sharia-Compliant Products - Ahmad Fauzi; Abdur Rafik (International Journal of Economics and Management Sciences, 2024)
This research examines the influence of sharia financial literacy on investment decisions in sharia financial products, by considering two moderating variables: perceived quality and religiosity. Quantitative methods were used by collecting data through bold questionnaires via Google Form to 190 respondents who understand sharia financial products. Data analysis was conducted using Structural Equation Modeling based on behavioral finance theory. The research results show that there is a positive influence of sharia financial literacy on investment decisions in sharia financial products. Perceived quality and religiosity do not moderate the influence of financial literacy on investment decisions, but have a direct effect. The implication is that sharia financial literacy influences positive investment decisions. Perceived quality and level of religiosity also influence investment decisions in sharia financial products. These findings are important for the Islamic finance industry in developing effective marketing and service strategies, as well as for educational institutions to increase sharia financial literacy.